Budidaya Tanaman Herbal Guna Meningkatkan Kesehatan Masyarakat Kota Batam - Fahlevi, Renza; Hasanah, Nafisatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The Community Service Program located in Tiban Baru area of ??Batam has two main objectives, namely applying herbal plant cultivation and conducting education to the public about the benefits of consuming herbal plants as medicines. The implementation of the service starts from July to August 2019 which includes the preparation stage, namely consolidation with the community. The implementation stage namely the stage of planting and cultivating herbal plants in the Tiban Baru district administered office in Batam city and the final stage is the treatment of herbal plants to grow as desired. The result of this program is the availability of plant seeds to be given to the community (PKK group) and the increasing desire of the community to use herbal plants as a way to live healthily.